Theater movement in Turkestan in late 19th – early 20th centuries - Umidjon U. Tojiboyev (Историческая этнология, 2025)
The article analyzes the national forms of theatrical art that existed in Turkestan in the pre-imperial and early period of the Russian Empire. The author shows the essence of the folk humorous art and clownery that existed in the region and points out how theatrical traditions changed under the influence of external factors. Rich, centuries-old traditions of folk theater in Turkestan have been presented. It is proved that after the conquest of the region by the Russian Empire, many changes took place in all its regions and were aimed at promoting the interests of the new government. This policy consisted in promoting European, Russian music and theatrical art. At the same time, Tatar and Azerbaijani theaters and artists began to come to Turkestan on tour, showed productions, and exchanged experience with local theater figures. Information about the repertoire of visiting and local theater troupes have been provided. The paper draws particular attention to the role of the Jadids in the formation of progressive theater in Turkestan. The advanced national intelligentsia mastered new ideas in culture and changed the local society. The paper demonstrates the importance of theatrical art for the socio-political life of Turkestan, reveals the formation of the Uzbek Jadid theater, and outlines the stages of the European theatrical art formation in the region. It is concluded that the creation of professional theaters in Turkestan in late 19th – early 20th centuries was accompanied by state policy on regulating their activities. The attitude of representatives of the local population, the government of the Russian Empire, and the Turkestan Regional Security Department to the theater have been discussed.